Children and adolescents with speech sound disorders are more likely to have orofacial dysfunction and malocclusion - Åsa Mogren; Anders Sand; Christina Havner; Lotta Sjögreen; Anna Westerlund; Monica Barr Agholme; Anita Mcallister (Wiley, 2022)
Abstract Background Children with speech sound disorders (SSD) form a heterogeneous group that differs in terms of underlying cause and severity of speech difficulties. Orofacial dysfunction and malocclusions have been reported in children with SSD. However, the association is not fully explored. Objectives Our aims were to describe differences in orofacial function and malocclusion between a group of children and adolescents with compared to without SSD and to explore associations between those parameters among the group with SSD. Methods A total of 105 participants were included, 61 children with SSD (6.0-16.7 years, mean age 8.5 ± 2.8, 14 girls and 47 boys) and 44 children with typical speech development (TSD) (6.0-12.2 years, mean age 8.8 ± 1.6, 19 girls and 25 boys). Assessments of orofacial function included an orofacial screening test and assessment of bite force, jaw stability, chewing efficiency, and intraoral sensory‐motor function. Possible malocclusions were also assessed. Result Children with SSD had both poorer orofacial function and a greater prevalence of malocclusion than children with TSD. Furthermore, children with SSD and poorer orofacial function had a greater risk of malocclusion. Conclusion Our result suggests that children with SSD are more prone to having poorer orofacial function and malocclusion than children with TSD. This illustrates the importance of assessing coexisting orofacial characteristics in children with SSD, especially since orofacial dysfunction may be linked to an increased risk of malocclusion. This result highlights the need for a multiprofessional approach.